Circulating FGF21 and GDF15 as Biomarkers for Screening, Diagnosis, and Severity Assessment of Primary Mitochondrial Disorders in Children - Li, Yi; Li, Shengrui; Qiu, Yinfeng; Zhou, Maobin; Chen, Min; Hu, Yue; Hong, Siqi; Jiang, Li; Guo, Yi (Frontiers in Pediatrics, 2022)
Background: Primary mitochondrial disorders (PMDs) are a diagnostic challenge for paediatricians, and the identification of reliable and easily measurable biomarkers has become a high priority. This study aimed to investigate the role of serum fibroblast growth factor 21 (FGF21) and growth differentiation factor 15 (GDF15) in children with PMDs. Methods: We analysed serum FGF21 and GDF15 concentrations by ELISA in children with PMDs, non-mitochondrial neuromuscular disorders (NMDs) patients and aged-matched healthy children and compared them with serum lactate and the ratio of lactate/pyruvate (L/P). We also evaluated the correlations between these biomarkers and the phenotype, genotype and severity of PMDs. Results: The median serum GDF15 and FGF21 concentrations were significantly elevated in fifty-one patients with PMDs (919.46 pg/ml and 281.30 pg/ml) compared with thirty patients with NMDs(294.86 pg/ml and 140.51 pg/ml, both P<0.05) and fifty healthy controls (221.21 pg/ml and 85.02 pg/ml, both P< 0.05). The area under the curve of GDF15 for the diagnosis of PMDs was 0.891, which was higher than those of the other biomarkers, including FGF21 (0.814), lactate (0.863) and the L/P ratio (0.671). Calculated by the maximum Youden index, the critical value of GDF15 was 606.369 pg/ml, and the corresponding sensitivity and specificity were 74.5% and 100%. In the PMDs group, FGF21 was significantly correlated with the International Paediatric Mitochondrial Disease Scale (IPMDS) score. The levels of GDF15 and FGF21 were positively correlated with age, critical illness condition and multisystem involvement but were not correlated with syndromic/nonsyndromic PMDs, different mitochondrial syndromes, nuclear DNA/mitochondrial DNA pathogenic variants, gene functions, or different organ/system involvement. Conclusion: Regardless of the clinical phenotype and genotype, circulating GDF15 and FGF21 are reliable biomarkers for children with PMDs. GDF15 can serve as a screening biomarker for diagnosis, and FGF21 can serve as a severity biomarker for monitoring.